1984
DOI: 10.1083/jcb.99.5.1872
|View full text |Cite
|
Sign up to set email alerts
|

Expression of unusually large keratins during terminal differentiation: balance of type I and type II keratins is not disrupted.

Abstract: When a basal epidermal cell undergoes a commitment to terminally differentiate, it ceases to divide and begins to migrate outward towards the surface of the skin. Dramatic changes in its cytoskeletal architecture take place, accompanied by numerous changes in the expression of keratins, a family of related polypeptides that form 8-nm filaments in these cells. We show here that a shift to the synthesis of unusually large keratins occurs that does not seem to disrupt the ratio of two distinct subfamilies of kera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
2

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 44 publications
2
8
2
Order By: Relevance
“…Roughly equimolar amounts of type I and type II CKs are expressed in these cells (Fig. 2, A), which is consistent with previous observations (Kim et al, 1984). In this simplistic model, we regarded CKs as being in a filament form (i.e., insoluble), although a small fraction (~5%) of the total CK has been reported to be soluble (Chou et al, 1993).…”
Section: Mechanisms For Maintaining Cytokeratin Filament Networksupporting
confidence: 89%
“…Roughly equimolar amounts of type I and type II CKs are expressed in these cells (Fig. 2, A), which is consistent with previous observations (Kim et al, 1984). In this simplistic model, we regarded CKs as being in a filament form (i.e., insoluble), although a small fraction (~5%) of the total CK has been reported to be soluble (Chou et al, 1993).…”
Section: Mechanisms For Maintaining Cytokeratin Filament Networksupporting
confidence: 89%
“…To our knowledge, the only IF protein gene that has been characterized is that for hamster vimentin (15), but despite the paucity of information, it is nevertheless interesting to compare the exon/intron structure of this keratin and that of vimentin. ------A-----I 503 528 (39) have suggested that the mRNA for the human 67-kDa type II keratin is 3.8 kb long, based on blot analysis with a nonspecific type II cDNA clone. The complete structure of this gene, reported here, shows that its mRNA is actually about 2.5 kb long.…”
Section: G S G Y R S G G G F S F G F a G I I N Y Q R R T T S S S T R mentioning
confidence: 99%
“…K1 and K10 are markers for differentiation and are only expressed in well-differentiated, suprabasal cells [1, 2]. K6/K16 is a keratin pair which is expressed in hyperproliferative cells and it is also found suprabasally [3, 4]. There is experimental evidence that in psoriasis the keratin K1/K10 pair is down-regulated when expression of the keratin K6/K16 pair is induced [5, 6], a relationship which has also been described for other skin conditions [7, 8].…”
Section: Introductionmentioning
confidence: 99%